Mechanized wet direct seeding for increased rice production efficiency and reduced carbon footprint - Nguyen, Hung; Thach, Tran Ngoc; Nguyen, Ngoc Hoang; Binh, Nuguyen Cao Quan; Dang Minh Tâm; Tran Tan Hau; Duong Thi Tu Anh; Trinh Quang Khuong; Vo Thi Bich Chi; Truong Thi Kieu Lien; Gummert, Martin; Rakotoson, Tovohery; et al. (Springer, 2024)
Crop establishment is one of the major rice production operations that strongly affects rice production, productivity, and environmental impacts. This research introduced a new technology and provided scientific evidence for the benefits of mechanized wet direct seeding (mDSR) of rice as compared with the other crop establishment practices commonly applied by farmers for wet direct seeded rice in Mekong River Delta in Vietnam, such as seeding in line using drum-seeder (dDSR) and broadcast seeding (bDSR). The experiment was implemented across two consecutive rice cropping seasons that are Winter-Spring season and Summer-Autumn season in 2020–2021. Treatments included (1–3) mDSR with seeding rates of 30, 50, and 70 kg ha− 1, (4) dDSR with 80 kg ha− 1 seed rate, and (5) bDSR as current farmer practice with seeding rate of 180 kg ha− 1. The fertilizer application was adjusted as per seeding rate with 80:40:30 kg ha− 1 N: P2O5: K2O with lower seed rate 30 and 50 kg ha− 1 in mDSR; 90:40:30 kg ha− 1 N: P2O5: K2O with medium seed rate of 70 to 80 kg ha− 1; and 115:55:40 kg ha− 1 N: P2O5: K2O with high seed rate of 180 kg ha− 1 in bDSR. Mechanized wet direct seeding rice with a lower seed rate of 30 to 70 kg ha− 1 and fertilizer rate by 22–30% reduced variation in seedling density by 40–80% and in yield by 0.1 to 0.3 t ha− 1 and had similar yield to bDSR. In consequence, N productivity was 27 and 32% higher in mDSR as compared to bDSR during the Winter-Spring season and Summer-Autumn seasons, respectively. The use of lower seed rate and fertilizer in mDSR also led to higher income and lower carbon footprint (GHGe per kg of paddy grains) of rice production than the currently used practices of bDSR. Net income of mDSR was comparable to that of dDSR and higher by 145–220 and 171–248 $US than that of bDSR in Winter-Spring season and Summer-Autumn, respectively. The carbon footprint of mDSR rice production compared to bDSR was lower by 22–25% and 12–20% during the Winter-Spring and Summer-Autumn seasons, respectively. Given the above benefits of farming efficiency, higher income, and low emission, mDSR would be a technology package that strongly supports sustainable rice cultivation transformation for the Mekong River Delta of Vietnam.